2021
DOI: 10.1371/journal.pone.0250685
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Chinese herbal footbaths for the treatment of dysmenorrhea: Protocol for a systematic review and meta-analysis

Abstract: Background Chinese herbal footbaths are an external therapy of traditional Chinese medicine that has been widely used to treat dysmenorrhea. This review aims to systematically evaluate its efficacy and safety for the treatment of dysmenorrhea. Methods Databases of PubMed, EMBASE, Cochrane Library, CIHAHL, Web of Science, Chinese National Knowledge Infrastructure(CNKI), Chinese Scientific Journals Database (VIP), Wanfang Database, China Biomedical Literature Database(CBM), and Chinese Biomedical Literature Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In severe cases, around 3% to 33% of women even have the problem of not being able to go to work or school for 1 to 3 days. For these reasons, it is reported to be a public health issue with socioeconomic effects 33–36 . Similarly, the women in this study were found to be highly affected by dysmenorrhea functionally and emotionally (44.50 ± 14.17).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In severe cases, around 3% to 33% of women even have the problem of not being able to go to work or school for 1 to 3 days. For these reasons, it is reported to be a public health issue with socioeconomic effects 33–36 . Similarly, the women in this study were found to be highly affected by dysmenorrhea functionally and emotionally (44.50 ± 14.17).…”
Section: Discussionsupporting
confidence: 68%
“…For these reasons, it is reported to be a public health issue with socioeconomic effects. [33][34][35][36] Similarly, the women in this study were found to be highly affected by dysmenorrhea functionally and emotionally (44.50 ± 14.17). Many studies in the literature have shown that risk factors in many aspects such as biological (early menarche age, heavier menstruation, and dysmenorrhea history in family).…”
Section: Discussionmentioning
confidence: 73%